Cardiovascular and Venous Thromboembolic Risk With Janus Kinase Inhibitors in Immune‐Mediated Inflammatory Diseases: A Systematic Review and Meta‐Analysis of Randomized Trials. Issue 10 (28th July 2022) - Maqsood, Muhammad Haisum; Weber, Brittany N.; Haberman, Rebecca H.; Lo Sicco, Kristen I.; Bangalore, Sripal; Garshick, Michael S.
Abstract : Objective: Janus kinase (JAK) inhibition effectively treats immune‐mediated inflammatory diseases (IMIDs); however, concern over the risk of major adverse cardiac events (MACE) and venous thromboembolism (VTE) remains. We aimed to evaluate the safety (VTE and MACE outcomes) of JAK inhibitors in the treatment of IMIDs. Methods: A search in PubMed, Embase, and ClinicalTrials.gov databases was conducted for randomized clinical trials (RCTs) of JAK inhibitors across IMIDs. Primary outcomes were VTE and MACE with JAK inhibitors compared with placebo and active comparator arms stratified by follow‐up time. Results: Sixty‐six RCTs enrolled 38, 574 patients with a mean age of 48.8 years and a mean follow‐up of 10.5 months. JAK inhibitors had a numerically higher rate of VTE when compared with controls (odds ratio [OR] 1.65; 95% confidence interval [CI]: 0.97‐2.79), driven by trials with a follow‐up duration of 12 or more months (OR 2.17; 95% CI: 1.16‐4.05; P interaction  = 0.05). When compared with active comparators, JAK inhibitors increased VTE in clinical trials with 12 or more months' versus less than 12 months' follow‐up time (OR 2.38 [95% CI: 1.24‐4.57] vs 0.30 [95% CI: 0.07‐1.26], respectively; P interaction  = 0.01). No increased risk of VTE was seen when comparing JAK inhibitors with placebo arms. For the outcome of MACE, the results were largely similar but did not reach statistical significance (OR 1.19; 95% CI: 0.86‐1.64). Conclusion: JAK inhibitors when compared with active comparator arms increased the risk of VTE, which was dependent on duration of exposure. Future clinical trials with extended follow‐up are needed to clarify the safety profiles of JAK inhibitors.